Organización Contable y Tributaria de la Farmacia Santa Fe sucursal 2 periodo enero-marzo 2016 - Erreyes Medina, Erika Yasmin (2017)
This thesis titled ACCOUNTANT AND ORGANIZATION TAX PHARMACY SANRA FE BRANCH 2 PERIOD JANUARY MARCH 2016. Is oriented to apply the accounting tools to improve its efficient development and development of the company under study which is dedicated to the purchase and sale of pharmaceutical products which is located in the city of Loja, so that the owner Is aware of the economic-financial situation in a given period was carried out by implementing each of the specific objectives that were proposed in an effective and timely manner, thus facilitating decision-making. The compilation and organization of all the accounting information required will serve to develop the accounting process in the period under study. The objectives were fulfilled as the investigative process was developed; Finding concrete solutions to the shortcomings detected in accounting control, which will make it easier for the owner to make timely decisions for the development of the company. The accounting control is performed through the multiple account system, was carried out with the supporting documentation provided by the owner of the company, starting from the initial inventory the plan and manual of accounts, State of Initial Situation, also elaborated the: Auxiliary Of Purchases and Sales Roles of Payments and Social Provisions, thus elaborating the daily book, book, 5 major, checking balance, worksheet, adjustments, until determining the respective financial statements such as: Income Statement, Statement of Financial Position and State Of Cash Flow, based on the Ecuadorian Accounting Standards. Finally, the application of financial indicators was carried out with their respective quantitative analysis which allowed to know the operating profitability and determined the economic financial behavior of the company. With the culmination of this thesis work, it is left the proposal and importance of the implementation of commercial accounting under the multiple account system and the application of financial indicators in the "PHARMACY SANTA FE BRANCH 2", for the development of its activities Commercial activities which will enable it to have real, effective and timely information on the business's progress, in addition to the organization and registration of the economic movements that were obtained during the period January to March, it was determined that the company has utility in its economic activity Which can be capitalized to improve its profitability 6 c) INTRODUCCIÓN La Contabilidad Comercial es fundamental en el desarrollo empresarial, puesto que nace de las relaciones comerciales y de servicios entre dos o más personas, de ahí que la aplicación de una adecuada organización contable es necesario e importante que permita manejar sus recursos correcta y adecuadamente ya que se ha convertido en una herramienta importante que permite registrar de forma ordenada sus actividades periódicas y generar información oportuna, confiable y de esta manera contribuya a fortalecer la gestión institucional, mejorando esencialmente a su desarrollo con una mayor productividad y aprovechamiento eficiente de sus recursos. El propósito del presente trabajo es brindar un aporte a la propietaria a través de la implantación de una organización contable que le permita organizar las actividades comerciales y de esta manera obtener información económica-financiera de manera eficiente, confiable y oportuna originando una visión clara del grado de eficiencia y rentabilidad, por lo tanto le servirá como una guía a la propietaria para la orientación sobre el proceso contable y a la vez demostrarle cuán importante es saber administrar un